2022
DOI: 10.3389/fmicb.2022.920117
|View full text |Cite
|
Sign up to set email alerts
|

Complete identity and expression of StfZ, the cis-antisense RNA to the mRNA of the cell division gene ftsZ, in Escherichia coli

Abstract: Bacteria regulate FtsZ protein levels through transcriptional and translational mechanisms for proper cell division. A cis-antisense RNA, StfZ, produced from the ftsA-ftsZ intergenic region, was proposed to regulate FtsZ level in Escherichia coli. However, its structural identity remained unknown. In this study, we determined the complete sequence of StfZ and identified the isoforms and its promoters. We find that under native physiological conditions, StfZ is expressed at a 1:6 ratio of StfZ:ftsZ mRNA at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…It was shown that a two‐ to seven‐fold increase in FtsZ level results in mini‐cell formation, due to additional division events, whereas further higher levels or lower than normal levels cause filamentation due to imbalance in the FtsZ:FtsA stoichiometry. [ 24 ] Faithful nucleoid segregation, therefore, depends on a precise mechanism that ensures the equipartition of nucleoids among daughter cells as well as the coordination between DNA replication and cell division. [ 25 ] The best‐understood steps in the process of nucleoid segregation have proven to be the early ones that are required for decatenation and dimer resolution.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that a two‐ to seven‐fold increase in FtsZ level results in mini‐cell formation, due to additional division events, whereas further higher levels or lower than normal levels cause filamentation due to imbalance in the FtsZ:FtsA stoichiometry. [ 24 ] Faithful nucleoid segregation, therefore, depends on a precise mechanism that ensures the equipartition of nucleoids among daughter cells as well as the coordination between DNA replication and cell division. [ 25 ] The best‐understood steps in the process of nucleoid segregation have proven to be the early ones that are required for decatenation and dimer resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Posttranscriptional regulation of ftsZ is similarly complex and involves several cis - and trans -acting sRNAs. Specifically, three isoforms produced from consecutive promoters have been reported for the StfZ RNA that is located antisense to the ftsZ gene ( 72 , 73 ). Although StfZ overexpression reduces FtsZ protein levels, physiological conditions resulting in differential expression of the sRNA have not been identified, suggesting that StfZ might function by fine-tuning ftsZ mRNA levels, rather than blocking cell division in response to a distinct stress ( 72 ).…”
Section: Discussionmentioning
confidence: 99%